2018
DOI: 10.1136/tobaccocontrol-2018-054446
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationship of vaping to smoking initiation among US youth and young adults: a reality check

Abstract: BackgroundThe 2018 National Academies of Sciences, Engineering, and Medicine Report found substantial evidence that electronic cigarette use (vaping) by youth is strongly associated with an increased risk of ever using cigarettes (smoking) and moderately associated with progressing to more established smoking. However, the Report also noted that recent increases in vaping have been associated with declining rates of youth smoking. This paper examines the temporal relationship between vaping and youth smoking u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

16
130
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 174 publications
(153 citation statements)
references
References 44 publications
16
130
0
Order By: Relevance
“…Hence, this provides no evidence that smoking was becoming renormalised during this time and suggests that any gateway effects were not having a population level impact on smoking rates. Similar findings have been reported among older adolescents and young adults in the United States (US) [34]. However, newer generation high nicotine devices are gaining popularity among North American youth, while there is some evidence that smoking has also increased [35].…”
Section: Introductionsupporting
confidence: 78%
“…Hence, this provides no evidence that smoking was becoming renormalised during this time and suggests that any gateway effects were not having a population level impact on smoking rates. Similar findings have been reported among older adolescents and young adults in the United States (US) [34]. However, newer generation high nicotine devices are gaining popularity among North American youth, while there is some evidence that smoking has also increased [35].…”
Section: Introductionsupporting
confidence: 78%
“…Nevertheless, it is not clear whether e-cigarette use has kept some people from quitting cigarettes,45 since e-cigarette use is relatively recent and is relatively low among current smokers (4.7%) and former smokers (1.1%). Indeed, the introduction of e-cigarettes has been associated with a decline in youth and young adult smoking prevalence in other countries where e-cigarette use is more prevalent 46. To evaluate how e-cigarettes influence smoking patterns in Mexico, further research is needed, particularly on how lighter smokers use e-cigarettes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the present study was over 24 months and showed effects for ever smoking, any recent tobacco smoking and regular cigarette smoking (see 15 for similar results). Together, these studies suggest that it is unlikely that the high rates of dual use of e-cigarettes and smoking observed in the US [5][6][7][8] and UK [9][10][11] in cross-sectional surveys of adolescents are entirely attributable to cigarette users subsequently taking up e-cigarettes. In our sample, at follow-up approximately one-third (177/585=30.3%) of those who used both e-cigarettes and cigarettes reported using e-cigarettes first (a further 191/585=32.6% reported using cigarettes first, and the remainder 217/585=37.1% could not remember which they tried first).…”
Section: Discussionmentioning
confidence: 99%
“…A focus of attention has been on the role of e-cigarettes in smoking initiation. Recent cross-sectional surveys of cohorts in both the USA [5][6][7][8] and UK [9][10][11] have shown that adolescents' rates of ever use of e-cigarettes increased at the same time that rates of cigarette use decreased. In contrast, longitudinal surveys in adolescents show use of e-cigarettes to be associated with subsequent smoking initiation.…”
Section: Introductionmentioning
confidence: 99%